Efektivitas Game Edukatif Ular Tangga Materi Keberagaman Budaya Terhadap Prestasi Belajar IPAS Siswa Kelas IV SD - Sauma Putra, M Bima; Djunaidi; Eni Heldayani (Global Action and Education for Society, 2025)
Learning media is a tool used by teachers to deliver learning materials to students, either in the form of tools, resources, or devices that facilitate the learning process. One of the educational learning tools for snakes and ladders games is games. The purpose of this study was to determine the effectiveness of the snakes and ladders educational game on cultural diversity material on the science learning achievement of grade IV students of SDN 06 Palembang. The method used in this study is a quasi-experimental method with the Pre-Test and Post-Test with Non-Equivalent Control-Group Design design type. The sampling technique used purposive sampling which consisted of two classes, namely class IV. B and IV. C totaling 50 students. The posttest results obtained an average posttest score for class IV. B of 64 and IV. C of 57.2. Hypothesis testing of research data using independent sample t-test with the criteria that Ha is accepted if t count > t table. Obtained with a value of (t count) 2.034 > (t table) 1.677 and sig. (2 tailed) = 0.047 < 0.05, then from the calculation it shows that Ha is accepted, meaning there is an effectiveness of the educational game of snakes and ladders on cultural diversity material on the science learning achievement of grade IV students of SDN 06 Palembang.